Cystinosis symposium: a rare disease model for comprehensive care - Gefen, Ashley M.; Kaskel, Frederick J.; Zaritsky, Joshua J. (Frontiers in Pediatrics, 2025)
The time to provide a forum for collaboration in cystinosis research underscored the recent Cystinosis Symposium: A Rare Disease Model for Comprehensive Care held at the New York Academy of Medicine, on 31 May 2024, an event sponsored by the Cystinosis Research Network and numerous corporate entities (Amgen and others). This conference was one of the first to address the glaring deficiencies in the care of children and adults with cystinosis by focusing on themes that are mutually applicable to multidisciplinary healthcare providers, educators, and families. The ultimate goal was to disseminate new information and awareness to all engaged in the cystinosis community and provide an algorithm to navigate more effectively the promising future toward a cure.